2017
DOI: 10.1177/1460458217723169
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosing asthma and chronic obstructive pulmonary disease with machine learning

Abstract: This study examines the clinical decision support systems in healthcare, in particular about the prevention, diagnosis and treatment of respiratory diseases, such as Asthma and chronic obstructive pulmonary disease. The empirical pulmonology study of a representative sample (n = 132) attempts to identify the major factors that contribute to the diagnosis of these diseases. Machine learning results show that in chronic obstructive pulmonary disease's case, Random Forest classifier outperforms other techniques w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
64
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 94 publications
(67 citation statements)
references
References 21 publications
2
64
0
1
Order By: Relevance
“…We assessed the predictive performances of our models using three main measures: AUC, SEN, and SPE, all commonly used performance measures. 39,40 The classifier's sensitivity, also known as true positive rate (TPR), is defined as the ability to correctly identify the true value (TP) of the cases. In this study the metric measures the probability of correctly identifying high-cost patients.…”
Section: Methodsmentioning
confidence: 99%
“…We assessed the predictive performances of our models using three main measures: AUC, SEN, and SPE, all commonly used performance measures. 39,40 The classifier's sensitivity, also known as true positive rate (TPR), is defined as the ability to correctly identify the true value (TP) of the cases. In this study the metric measures the probability of correctly identifying high-cost patients.…”
Section: Methodsmentioning
confidence: 99%
“…The proposed model was tested using a 10-fold cross-validation procedure. The proposed model when compared with other decision tree models such as Decision Tree with Reduced Error Pruning Method and A combination of Naïve Bayes, Decision Tree and SVM showed accuracy of 86.53%, specificity 95.5% and sensitivity of 86.5% [29]. The CAD model used Least Squares SVM (LS-SVM) classifier which was when compared to other classifiers such as ANN, and Hidden Markov Models (HMM) showed accuracy, sensitivity and specificity of 95.39%, 96.59% and 93.75% respectively [30].A comparative study by Acharya [39] on heart disease prediction, used Heart Disease Data Set from UCI machine learning repository.…”
Section: Discussionmentioning
confidence: 97%
“…The prediction of lung diseases such as COPD and Asthma through classifier techniques. Study by Spathis and Vlamos [29] predicted Asthma and Chronic Obstructive Pulmonary Disease (COPD). Dataset consist of 132 subjects and the study reported that Random Forest outperforms other algorithms with precision rate of 97.7% for COPD and 80.3% for asthma.…”
Section: Asthma Copdmentioning
confidence: 99%
“…China has a high incidence of COPD, and with an increasing population, environment deterioration and prominent aging problem, the number of COPD patients complicated with pneumonia has also shown a growing trend ( 9 ). Alveolar lavage using antibiotics based on the bronchoscope technique has been widely applied in clinic to remove the lung mucus and control inflammation, which can effectively increase the treatment effective rate of COPD patients complicated with pneumonia, and reduce the inflammatory response ( 10 ). Fortún et al ( 11 ) treated the COPD patients complicated with type II respiratory failure using alveolar lavage combined with mechanical ventilation, and the results showed that CRP declined and blood gas analysis were significantly improved.…”
Section: Discussionmentioning
confidence: 99%